2016
DOI: 10.5194/isprsarchives-xli-b2-615-2016
|View full text |Cite
|
Sign up to set email alerts
|

Positional Accuracy Assessment of the Openstreetmap Buildings Layer Through Automatic Homologous Pairs Detection: The Method and a Case Study

Abstract: ABSTRACT:OpenStreetMap (OSM) is currently the largest openly licensed collection of geospatial data. Being OSM increasingly exploited in a variety of applications, research has placed great attention on the assessment of its quality. This work focuses on assessing the quality of OSM buildings. While most of the studies available in literature are limited to the evaluation of OSM building completeness, this work proposes an original approach to assess the positional accuracy of OSM buildings based on comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 4 publications
(6 reference statements)
0
19
0
Order By: Relevance
“…For example, it was found that completeness levels vary widely between different cities, e.g., between 12% and 48% for selected parts of Germany [19], and between 30% and 75% for three cities in the United Kingdom [20]. Completeness evaluation and positional accuracy assessment was also performed for Milan, Italy [21], which revealed a decreasing trend in completeness from the city center towards the outskirts. Positional accuracy was found to be similar across the city, probably due the constant accuracy of the underlying imagery from which buildings were traced.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that completeness levels vary widely between different cities, e.g., between 12% and 48% for selected parts of Germany [19], and between 30% and 75% for three cities in the United Kingdom [20]. Completeness evaluation and positional accuracy assessment was also performed for Milan, Italy [21], which revealed a decreasing trend in completeness from the city center towards the outskirts. Positional accuracy was found to be similar across the city, probably due the constant accuracy of the underlying imagery from which buildings were traced.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Brovelli et al [32] assessed the completeness and the positional accuracy in Milan (Italy) using, for the former, the area unit based approach with the computation of uncertainties already seen in other studies, and, for the latter, a new method based on the automatic matching of the points of the footprints. The work presented here is a step forward in the definition of this second approach, which aims at contributing to the debate about positional accuracy and completeness of OSM, a debate that is still open.…”
Section: Related Workmentioning
confidence: 99%
“…The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, Volume XLII-4/W8, 2018FOSS4G 2018-Academic Track, 29-31 August 2018, Dar es Salaam, Tanzania a higher average number of different contributors occurs when moving towards the centre. In this case, the maximum value is equal to 17.3.…”
Section: Aggregated Analysismentioning
confidence: 99%
“…Graser et al, 2014;Brovelli et al, 2016a), while less attention was paid to other thematic layers such as buildings (see e.g. Hecht et al, 2013;Fan et al, 2014;Brovelli et al, 2016b), land use (see e.g. Jokar Arsanjani et al, 2015b;Fonte et al, 2017) and points of interest (see e.g.…”
Section: Openstreetmap Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation